Pelatihan Aplikasi Penggunaan Matlab Untuk Meningkatkan Pengetahuan Guru - Yanie, Ahmad; Srg, Lisa Adriana; J, Junaidi (LPPM STIKOM Tunas Bangsa, 2019)
Nowadays the task of the teacher is felt to be getting tougher with the change in the curriculum used, which is to become a Competency Based Curriculum (CBC) with one of the existing learning methods namely Contextual Teaching Learning (CTL) learning. A learning using computer aids becomes an important requirement in learning with the CTL system, so it becomes a necessity for teachers to be able to master computer software that can help a learning. Software that can help learning mathematics in the classroom is MATLAB or Matrix Laboratory software, which is currently being used by teachers in mathematics and vocational engineering. To improve the ability of teachers to utilize computers in learning, especially in the use of MATLAB software, a